MPPT-controlled adaptive reconfigurable 5.8GHz RF energy harvesting front-end to extend operating range - Lopez, Aristotle D.
The range of input power levels that allow a RF energy harvester to produce an output level required to power a WSN node is limited, making it impractical to be combined with harvesters with more stable energy sources such as powerline in a multimode energy harvesting system. The limitation is caused by the losses arising from the configuration of the RF energy harvester that is not ideal for the input power level. A static RF energy harvester commonly designed for a certain range of input power level is limited in operating range and efficiency when used for RF sources where highly variable power levels are expected. A dynamic RF energy harvester that can be reconfigured to adapt to the input power level improves the operating range. The number of stages in the rectifier cascade and the input impedance produced by the matching network are modified to maximize the operating range. Since reconfigurable, the most efficient configuration of the RF energy harvester can also be set using a Maximum Power Point Tracking (MPPT) mechanism. Several configurations could produce the required output, but MPPT is used to choose the most efficient configuration for each input power level. This maximizes the power harvested from RF sources, allowing it to be combined with energy from more stable energy sources. Simulation results for a design implemented in 65nm CMOS process show an improvement of around 17dB in operating range and up to 20 percent in efficiency for a dynamic RF energy harvester implementing MPPT compared to a static RF energy harvester in producing a 1V output using a 5.8 GHz input.